Pemanfaatan m-Health Berbasis Kebutuhan Sistem Informasi pada Upaya Perkesmas: Kasus TBC - Hasti Primadilla (Journal of Telenursing (JOTING), 2022)
This study aims to produce an application prototype that utilizes mobile technology for family-based TB treatment in the Perkesmas effort. The method used is the SDLC approach with the PRISM framework model to identify problems with organizational, technical and behavioral factors that are all interrelated. The results showed that Puskesmas M and A nurses assessed a medium to high scale for the prototype utilization factor. The prototype can provide data on screening TB suspects in the family, monitoring the progress of TB treatment, medication adherence and re-control, and helpful information for TB research. In conclusion, the prototype produced can generally be accepted by Puskesmas nurses, especially in terms of the format and data variables provided. Keywords: Android, Home care, m-Health, Prototype, TB